The Influence of Plastic Deformation on the Corrosion Behavior of a Cast High‐Alloy CrMnNi TRIP Steel. Issue 8 (25th February 2016) - Mandel, Marcel; Böhme, Fabian; Hauser, Michael; Wendler, Marco; Tuchscheerer, Friedrich; Krüger, Lutz
Abstract : The influence of plastic deformation on the electrochemical corrosion behavior of a meta‐stable high‐alloy CrMnNi steel is investigated in a 5 wt% sodium chloride solution by cyclic voltammetry. Interrupted tensile tests are performed to attain two defined states of plastic deformation. The formation of straight slip bands and deformation‐induced α′‐martensite is observed in the austenite of the tensile samples which are deformed up to fracture. The deformation‐induced α′‐martensite fraction is evaluated by an in situ magnetic measurement method simultaneously to the tensile test. Microscopic observations after the potentiodynamic polarization revealed pitting corrosion at all surfaces. Furthermore, a strong dependency between applied anodic potential and degree of plastic deformation at forward polarization is found, whereas the reverse scan exhibits a significant influence of the pitting corrosion attack. Consequently, the forward polarization behavior is dictated by the previously applied mechanical stress, whereas the influence disappears when pits have been formed. Abstract : The electrochemical corrosion characteristic of a CrMnNi TRIP steel cast alloy is analyzed in dependence of plastic deformation in a 5 wt% sodium chloride solution. Cyclic voltammetry is carried out and reveals a strong dependency at forward polarization, whereas at reverse scan the behavior is dominated by pitting corrosion.